Empowering Compartmental Modeling With Mobility and Shelter-in-Place Analysis - Bakhtiari Ramezani, Somayeh; Rahimi, Shahram; Amirlatifi, Amin; Hudnall, Matthew; Pate, Jeremy; Parrish, Allen; Penmetsa, Praveena; Qian, Xinwu (Frontiers in Future Transportation, 2021)
A model that is capable of handling the non-linear trend of COVID-19 throughout the US and evaluate different effects of interstate/intrastate mobility measures can help decision-makers adjust guidelines and state-wide mandates to contain the pandemic’s spread. The abundance of cellular-based data has made it possible to study many aspects of users’ mobility, including their travel, contact, and dwell patterns. This study uses a compartmental metapopulation model to present a correlation between the contact and mobility indices and the likelihood of being susceptible to infection. We studied the effect of travel from other states on overall infections in a destination state and observed a strong inverse correlation of 0.98 between the contact index and social awareness compartment, i.e., individuals who are no longer susceptible to infection. The shelter-in-place what-if analysis for travelers from other states on the course of infection in the destination state showed a possible reduction of over 22% in the total number of infections and death if travelers sheltered in place for 5-7 days.